2013
DOI: 10.4312/dp.40.19
|View full text |Cite
|
Sign up to set email alerts
|

Will the real specialist please stand up? Characterising early craft specialisation, a comparative approach for Neolithic Anatolia

Abstract: The Neolithic period saw changes in production practices and the roles of individuals that were important in the development of increasing social differentiation. Although there is evidence of specialised manufacturing in Neolithic Anatolia, the dynamics of changing production and accompanying social effects have not been characterised. This article looks at how specialisation might be defined and identified in the Neolithic period in Anatolia using the results of recent theoretical debates as a starting point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…However, archaeological evidence of the last decades has increasingly shown that craft specialization did not follow a linear pattern of development interdependent with concurrent ‘progressions’ in social structure. Instead it waxed and waned for several millennia before institutionalized, centrally organized, consistent and long‐lived production became commonplace (Baysal ; Twigger ).…”
Section: Kanlitaş Bracelets and Early Craft Specializationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, archaeological evidence of the last decades has increasingly shown that craft specialization did not follow a linear pattern of development interdependent with concurrent ‘progressions’ in social structure. Instead it waxed and waned for several millennia before institutionalized, centrally organized, consistent and long‐lived production became commonplace (Baysal ; Twigger ).…”
Section: Kanlitaş Bracelets and Early Craft Specializationmentioning
confidence: 99%
“…In addition to the practical considerations of production, the social aspects are also important. For production to be specialized, there must be more consumers than there are producers, the product must be perceived to have a function, whether that is practical or social, and the object must be culturally congruent in some way and also form part of a socially specific typology (Twigger , 82–6; Baysal ). None of these parameters are without flexibility, and, depending on the specific context and even varying social conditions, they may be met to a greater or lesser extent.…”
Section: Kanlitaş Bracelets and Early Craft Specializationmentioning
confidence: 99%
“…There is limited evidence of inland use of Spondylus and Glycymeris in Anatolia, in contrast to sites in mainland Europe. At Canhasan I two possible examples of Glycymeris artefacts are reported from Chalcolithic layers dated to around 6000 cal bc (French 2010, 149), however there are more marine shells of species that have traditionally been associated with central Anatolia and the Near East such as Dentalium (Baysal 2009).…”
Section: The Cultural Milieu Of Spondylus Usementioning
confidence: 99%
“…As lithic analyses have grown more complex and precise, so too has the act of knapping and its application to the archaeological record. For example, mathematical modelling is becoming increasingly more complex in experimental lithic studies (Brantingham and Kuhn 2001;Lycett and Eren 2013a;2013b). Additionally, digital recording methods like two-and three-dimensional (2D and 3D) photogrammetry have markedly improved our ability to morphometrically compare experimental lithic specimens (Eren et al 2008;Grosman 2016;Heighway 2011;Muller and Clarkson 2016a;Sumner and Riddle 2008).…”
Section: Addressing Criticisms: Hypothesis Testing and Recent Trendsmentioning
confidence: 99%
“…Boncuklu Baysal 2013a;2013b;Fletcher et al 2017;Spataro et al in press) is an early Neolithic settlement mound in the Konya Plain of Central Anatolia, Turkey. The site is dated to 8,300-7,500 cal.…”
Section: Archaeological Case Study: Boncuklumentioning
confidence: 99%